EVALUATION OF MATERNAL AND PERINATAL OUTCOME IN WOMEN WITH BORDERLINE AFI AND OLIGOHYDRAMNIOS IN THIRD TRIMESTER: A TERTIARY CARE HOSPITAL-BASED STUDY - ARSHDEEP KAUR,; MANJIT KAUR MOHI,; PUNEET GAMBHIR,; MANJEET KAUR,; GURTEJ SINGH , (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Objectives of our study were (1) to study and compare obstetric outcome in women with oligohydramnios, borderline amniotic fluid index (AFI), and normal AFI in terms of (a) type of labor (spontaneous/induced) and (b) mode of delivery-C-section or vaginal delivery and (2) to study and compare perinatal outcome in women with oligohydramnios, borderline AFI, and normal AFI in terms of (a) prematurity, (b) APGAR score at 1 and 5 min, (c) fetal distress, (d) low birth weight, (e) weight for gestational age, (f) neonatal intensive care unit (NICU) admission, (g) cause of NICU admission, and (h) neonatal deaths. Methods: This prospective and comparative study was conducted in Rajindra Hospital Patiala, over a period of 1 year. Women with ≥34 weeks POG were subjected to ultrasonography. They were then divided into following three groups of 50 women each depending upon AFI: Group A – oligohydramnios (AFI <5 cm), Group B – borderline AFI (AFI 5–8 cm), and Group C – normal AFI (AFI >8–25 cm). Patients were followed up to 40 weeks POG or till delivery occurred or decision for C-section was taken. Results: Perinatal outcome was adversely affected by decrease in AFI in terms of increase in rate of preterm delivery, small for gestational age babies, low birth weight babies, and neonatal deaths. Conclusion: Measurement of AFI is an important tool for prediction of adverse neonatal outcome